Avaliação de características físico-químicas da carne de rã-touro (Lithobates catesbeianus) liofilizada de pigmentação normal e albina - Fragoso, Sinara Pereira (2012)
Frog meat show highlights because has the high value proteins biological and also low-fat because therefore has been considered as a dietary supplement and for treatment of various diseases and food allergy. It is necessary to obtain news products from frog meat to offer in the marked. Lyophilization of frog meat could be like an alternative for this problem because can add value in the innless parts noble, and we can have available and the excellent raw material for make some news products. The objectives of the present study were to: determine the composition of frog meat albino and pigmented normal; Post-mortem behavior from pH; and freeze-dry to study the meat from bullfrog aiming to offer it with high value protein and also the mineral value to obtain the specific food products. We used 150 bullfrogs (Lithobates catesbeianus). 75 were pigmented and 75 were albinos from the same spawn, males and females reared under Anfigraja separated into pens according to their own pigmentation. The animals were followed until it to obtain the weight of 230 ± 20 g, it happened in the February from to September 2011 (7 months). The method of killing was stunning electronarcosis with and without bleeding. Separation was performed and boning cuts according to the treatments. The sample were dry by until constant weight. The analyses were performed on fresh beef meat and lyophilized. We did in a 2x3 factorial (two cultivars x three cuts) with three replications in a completely randomized design. Manual boning was used to flank and thighbones and mechanics to the back. Frog albino had the higher initial pH for all sections except in the mechanically separated dorsal (DMS), the behavior was similar to the curves varieties, but not to the cuts, they were composed of muscles and different fiber composition that affect the pH value. Proximate food composition was similar for the two different frog albino and pigmented. The iron content was higher frog albino and show statistic difference from the normal pigmentation. Meat from bullfrog albino or pigmented in all courts had adopted the high protein content and mineral. For lyophilized samples range factor was only significant influence in determining the goal of color lyophilized meat. The cuts differ in composition, and the thigh and flank cuts more similar, with higher amounts of protein, and the back always different from the others with the highest percentage of lipids. The water solubility was determined not influenced by the factors studied, so the parameter to choice of which one treatment to use in developing a product with this raw material will depend on their physicochemical properties. The freeze-dried frog meat can be considered like an excellent ingredient to enrichment and the production the protein foods for specific purposes.